Relación entre los estilos de aprendizaje basados en el modelo de kolb y la mediación didáctica en función del desempeño académico estudiantil (2019)
The relationship between learning styles based on the Kolb model and didactic mediation based on student academic performance, correspond to the set of activities to use, share and develop the knowledge that has an educational community. For this reason, this research is based on the theory of David Kolb (1984 a, b), who developed a learning model through experience in the learning process itself. The aim of this paper is to analyze the relationship between learning styles based on the Kolb model and didactic mediation in terms of academic performance in university students. In this, a mixed paradigm is proposed, a Rationalist Deductive approach and a qualitative-quantitative paradigm. It was framed within the documentary and field design and develops a descriptive analysis on the learning styles presented by the students of the Bachelor Programs in Preschool Education and Computer Science Degree of the Faculty of Educational Sciences of the Universidad del Magdalena, which they take the subject "Science, Technology and Society" and the declared technique is the content analysis. Among the results, the most important factor weight when applying the Kolb Inventory corresponds to the CA-EC (Concrete-Abstract) dimension and the lowest to the EA-OR dimension (Activity-Reflection). In conclusion, the factorial composition found in the items confirms the theoretical proposal since both factors saturate both items positively and negatively, and constitute the 2 basic dimensions of the model (Concrete-Abstract and Experimentation-Observation)